Atención al cliente en el Comercial Joselito en el cantón Baba en el periodo 2023. - Villao Espinoza, Yulexy Jissette (2025)
Customer service is essential for the success and growth of any business, especially in local commerce, which faces constant challenges. The case study called “Customer service at the Joselito Commercial in the Baba Canton in the period 2023, in which a lack of adequate guidelines and a deficiency in customer service have been identified, generating economic losses and affecting the consumer experience, limiting the growth and sustainability of the business. The main objective of the study is to reorganize customer service at the Joselito commercial center in the Baba canton during the 2023 period to increase efficiency in the resolution of claims by increasing customer loyalty, which is why the Financial, Administrative, Tax, Audit and Control Management research line is used, which covers the study and develops strategies and methodologies that allow the effective management of financial and operational resources and the articulation of the topic related to the pre-professional internship project carried out around the Application of administrative or commercial processes in public or private institutions by which the satisfaction obtained with customer service could be determined. The results determined that there is a significant opportunity to improve the quality of customer service and provide a better satisfaction experience, concluding that ineffective communication and long wait times affect customer satisfaction, which is why the implementation of training programs for staff, the automation of operational processes, the design of standardized service protocols and loyalty strategies such as reward programs are recommended.